The Value of Use of Innovative Ideas for Intensification of Mental Activity of Students - Abdullaeva Umidahon Oktamjon qizi; Melikuzieva Zulhumor Sherqo’zi qizi; Nazirova Arofatxon Maxmudjon qizi (Zien Journals, 2022)
Modern pedagogical technologies have great potential to improve the efficiency of the pedagogical process, save time and energy. The correct and purposeful use of these opportunities makes it possible to implement a technological approach to the pedagogical process and achieve the main goal of social education - the formation of a harmoniously developed personality
Keywords: social education; socio-political activity; humanization